Deciphering cardiac involvement in systemic inflammatory diseases: noninvasive tissue characterisation using cardiac magnetic resonance is key to improved patients' care. (1st November 2016) - Gerster, Martin; Peker, Elif; Nagel, Eike; Puntmann, Valentina O.
ABSTRACT: Introduction : Cardiac involvement in systemic inflammatory diseases (SID) has a major impact on patients' morbidity and mortality, yet the pathways to its recognition and management remain poorly established. Areas covered : Overall clinical management in SID patients is primarily guided by systemic symptoms. Cardiovascular disease goes largely undetected, as it evolves through years of a protracted and subclinical course. Despite the increased awareness and insights into the mechanistic role of the inflammatory pathways, clinical management of cardiac involvement continues to rely on diagnostic means, which are frequently insensitive, invasive and rely on radiation exposure. Advanced tissue characterisation with cardiovascular magnetic resonance (CMR) offers an accurate, non-invasive and radiation-free diagnostic method with obvious advantages: it is able to inform on a range of cardiovascular pathophysiology, as well as support safe serial examinations, informing on the disease presence, progress and response to treatment. Expert commentary : We summarise the recent advances in non-invasive imaging, and bridge the novel insights into pathophysiology with future posibilities in diagnosis and manangement of SID patients. We propose an interdisciplinary framework to screening of cardiac involvement in SID using an indepth phenotyping of evolution of cardiovascular disease, to decipher the opportunities to improve patients' cardiac care.